Voragonema tatsunoko (Trachymedusae: Rhopalonematidae), a new species of benthopelagic medusa, host to the hyperiid amphipod Mimonectes spandli (Physosomata: Mimonectidae) - Lindsay, Dhugal; Pagès, Francesc (Zootaxa, 2010)
Large numbers of a distinctive trachymedusa were observed at 1967 m depth just above the bottom in Suruga Bay, Japan, during a dive by the crewed submersible Shinkai 2000 in April 2002. Two individuals were collected and proved to be an undescribed species, herein described as Voragonema tatsunoko sp. nov. This species is characterised by the number (9) and shape of the centripetal canals. An immature male hyperiid amphipod, Mimonectes spandli Stephensen and Pirlot, 1931, was observed attached to the subumbrella of one of the individuals adjacent to a gonad. This is the first record identifying an association between another organism and M. spandli and is the first record of this amphipod species outside of the Atlantic Ocean.